2021
DOI: 10.3390/su13020683
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of Sustainable Medical Tourism Destinations in Iran: An Integrated Approach Using Fuzzy SWARA-PROMETHEE

Abstract: Today, medical tourism is one of the fastest growing sectors of the tourism industry around the world. Medical tourism can contribute to the sustainable development and economic dynamism of countries. Therefore, in this study, we prioritize the world’s leading countries in medical tourism for Iranians. First, five main criteria and 20 sub-criteria were selected, which are the reasons for choosing a country as a medical tourism destination. In this paper a combined fuzzy SWARA-PROMETHEE approach was used to pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 83 publications
(91 reference statements)
0
21
0
Order By: Relevance
“…Some examples of the application of the fuzzy SWARA method with an inadequate scale were given in studies [37][38][39][40]. It should be noted that the future application of the fuzzy SWARA method should be replaced by the improved fuzzy SWARA (IMF SWARA) method or the application of another scale in fuzzy SWARA that eliminates these previously observed shortcomings.…”
Section: Improved Fuzzy Swara Methods (Imf Swara)mentioning
confidence: 99%
“…Some examples of the application of the fuzzy SWARA method with an inadequate scale were given in studies [37][38][39][40]. It should be noted that the future application of the fuzzy SWARA method should be replaced by the improved fuzzy SWARA (IMF SWARA) method or the application of another scale in fuzzy SWARA that eliminates these previously observed shortcomings.…”
Section: Improved Fuzzy Swara Methods (Imf Swara)mentioning
confidence: 99%
“…While the initial two strategies represented resilience, the third strategy demonstrated lack of resilience. Ghasemi et al (2021) revealed that sustainable criteria cover all economic, social, and environmental dimensions. Moreover, Qaiser Gillani et al (2021) highlighted the fact that a healthy environment results in healthy people and sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The decision problems may comprise various goals: to find the best alternative, to separate the alternatives into groups such as acceptable and unacceptable alternatives or good/bad; dominated and non-dominated, to find the clusters with similar or indifferent alternatives, or to create an order of alternatives (Ishizaka and Nemery 2013 ). The ranking may cover countries or regions (Ghasemi et al 2021 ; Stankovic et al 2021 ; Roszkowska and Filipowicz-Chomko 2020 ; Ulutaş and Karaköy 2019 ; Kuncova and Seknickova 2018 ; Kramulova and Jablonsky 2016 ; Latuszynska 2014 ; Kuncova and Doucek 2011 ; Dincer 2011 ), universities (Wu et al 2012 ), institutions as banks, start-up or public benefit organizations (Beheshtinia and Omidi 2017 ; Górecka and Chojnacka 2017 ; Nikoloudis et al 2017 ), renewable energy resources, energy pathways or energy technologies (Seknickova and Jablonsky 2020 ; Lee and Chang 2018 ; Schröder et al 2019 ; Regös 2013 ), materials or machines (Karande et al 2016 ; Chatterjee and Chakraborty 2012 ), product (Turcksin et al 2011 ), websites (Shayganmehr and Montazer 2021 ), people (Alguliyev et al 2019 ) and others.…”
Section: Introductionmentioning
confidence: 99%
“…If the goal of the decision problem is to rank alternatives, it is necessary to select a method for the solution that provides this type of result. Methods that have been used to obtain a complete arrangement of alternatives include, for example, WSA—Weighted Sum Approach, WSM—Weighted Sum Method (Lee and Chang 2018 ; Dincer 2011 ), WASPAS—Weighted Aggregated Sum Product Assessment (Karande et al 2016 ), SWARA—Stepwise Weight Assessment Ratio Analysis (Ghasemi et al 2021 ), VIKOR—VIseKriterijumska Optimizacija i kompromisno Resenje (Lee and Chang 2018 ; Wu et al 2012 ), AHP—Analytic Hierarchy Process (Shayganmehr and Montazer 2021 ; Beheshtinia and Omidi 2017 ; Kramulova and Jablonsky 2016 ; Wu et al 2012 ), TOPSIS—Technique for Order of Preference by Similarity to Ideal Solution (Lee and Chang 2018 ; Latuszynska 2014 ; Kuncova and Doucek 2011 ), some modifications of the ELECTRE methods—ELimination Et Choix Traduisant la REalité, such as modified ELECTRE II (Lee and Chang 2018 ) or modified ELECTRE III (Kuncova and Seknickova 2013 , 2018 , 2020 ), or the PROMETHEE II method—Preference Ranking Organization METHod for Enrichment Evaluations (Ghasemi et al 2021 ; Shayganmehr and Montazer 2021 ; Stankovic et al 2021 ; Seknickova and Jablonsky 2020 ; Schröder et al 2019 ; Nikoloudis et al 2017 ; Regös 2013 ; Turcksin et al 2011 ; Koutroumanidis et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation